Comparison of TSP measurements by two hi-vol samplers located side by side - Mohd. Yusoff, Mohd. Rashid (1987)
A simultaneous sampling of total suspended particulate (TSP) matter by two hi-vol air samplers located side by side were studied. The mean TSP concentrations samplers over 20 sampling days were 66.3 Î¼g/m3 and 68.2 Î¼g/m3. Both TSP concentrations were highly correlated (r = 0.975) with the regression line forced through the origin. This suggests that a consistent TSP measurement can be obtained using two hi-vol samplers located at one site.